2013
DOI: 10.1371/journal.pone.0060775
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase Magnesium-Dependent 1δ (PPM1D) mRNA Expression Is a Prognosis Marker for Hepatocellular Carcinoma

Abstract: BackgroundProtein phosphatase magnesium-dependent 1δ (PPM1D) is an oncogene, overexpressed in many solid tumors, including ovarian cancer and breast cancer. The current study examined the expression and the prognostic value of PPM1D mRNA in human hepatocellular carcinoma (HCC).MethodsTotal RNA was extracted from 86 HCC and paired non-cancerous liver tissues. PPM1D mRNA expression was determined by real-time quantitative reverse transcriptase-polymerase chain reaction (qPCR). Immunohistochemistry assay was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…PPM1D is a stress-responsive PP2C phosphatase that plays a key role in stress signaling (35). In addition, it was suggested that PPM1D is associated with carcinogenesis (36,37). It negatively regulates the DNA damage response through the dephosphorylation and inactivation of p53, ataxia telangiectasia mutated, p38 and checkpoint kinase 1/2 (38).…”
Section: Discussionmentioning
confidence: 99%
“…PPM1D is a stress-responsive PP2C phosphatase that plays a key role in stress signaling (35). In addition, it was suggested that PPM1D is associated with carcinogenesis (36,37). It negatively regulates the DNA damage response through the dephosphorylation and inactivation of p53, ataxia telangiectasia mutated, p38 and checkpoint kinase 1/2 (38).…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of previous observations also con rmed PPM1D overexpression in mouse embryonic broblasts and in promoting the development of tumors [23][24][25]. Furthermore, in hepatocellular carcinoma, enhanced PPM1D mRNA expression was related to clinical pathological factors and unfavorable prognosis, suggesting as a potential predictor for overall survival of the disease [26]. Yang and his colleagues have also demonstrated that PPM1D was highly expressed in non small cell lung cancer, and associated with the development of this cancer, indicating as an independent prognostic marker [13].…”
Section: Discussionmentioning
confidence: 76%
“…Notably, high levels of PPMD1 mRNA correlated with tumor size and stage and with poor patient's prognosis. Thus PPMD1 can be considered an interesting potential marker of HCC progression [46] .…”
Section: Protein Phosphatase Magnesium-dependent 1 Deltamentioning
confidence: 99%